USE OF ACCOUNTING FOR THE PHILOSOPHY OF EQUIVALENT PRODUCT PRODUCTION AND PERIOD IN THE PREPARATION OF FINAL RESULTS AND MANAGEMENT OF FIXED RESOURCES - Gnan Abed Kachi, Malath Abdul Jabbar Abbas, Hussein Ali Hisab, Deepali Sahni (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study focuses on the study of the technology of production, with the statement of the management of the results in the form of the balance sheet. The next hypothesis has been formulated: the use of administrative accounting for the philosophy of equivalent product production may facilitate the establishment of result-oriented reserves and the management of fixed resources. The subject matter of the discussion is the formation of Kufa Cement, a single formation of a public company for Southern Cement, and the implementation of the research in the practice of the final financial statements on 31/12/2019. The research reached a set of conclusions, the most important of which are: The philosophy of optimal production technology is a standard approach to dealing with the company through an integrated holistic view for the purpose of identifying and dealing with the constraints that the system faces. The productive mix and managing constrained resources.